Falling labor share and rising unemployment: Long-run consequences of institutional shocks? - Norbert Berthold; Rainer Fehn; Eric Thode (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 1999)
The literature on unemployment has mostly focused on labor market issues while the impact of capital formation is largely neglected. Job-creation is often thought to be a matter of encouraging more employment on a given capital stock. In contrast, this paper explicitly deals with the long-run consequences of institutional shocks on capital formation and employment. It is shown that the usual trade off between employment and wages disappears in the long run. In line with an appropriation model, the estimated values for the long-run elasticities of substitution between capital and labor for Germany and France are substantially greater than one.
Keywords: E23; E24; E25; J6; O3; 330; Unemployment; Institutional Shocks; Appropriation; Elasticity of Substitution; Technical Change; Arbeitslosigkeit; Lohnquote; Schock; Arbeitsmarkt; Institutioneller Wandel; Faktorsubstitution; Kapitalintensität; Wirtschaftswachstum; Theorie